Nucleofection induces transient eIF2α phosphorylation by GCN2 and PERK - Anderson, B R; Karikó, K; Weissman, D (Gene therapy, 2013)
Nucleofection permits efficient transfection even with difficult cell types such as primary and non-dividing cells, and is used to deliver various nucleic acids, including DNA, mRNA, and small interfering RNA. Unlike DNA and small interfering RNA, mRNA is subject to rapid degradation, which necessitates instant early translation following mRNA delivery. We examined the factors that are important in translation following nucleofection and observed rapid phosphorylation of eukaryotic initiation factor 2 alpha (eIF2α) following nucleofection, which occurred in the absence of the delivered nucleic acid. We studied the involvement of three ubiquitous kinases capable of phosphorylating eIF2α in mammalian cells and identified that nucleofection-mediated phosphorylation of eIF2α was dependent on general control non-derepressible 2 (GCN2) and RNA-dependent protein kinase (PKR)-like endoplasmic reticulum kinase (PERK) but not PKR. A reduction in translation due to eIF2α phosphorylation was observed post nucleofection, demonstrating functional significance. Understanding the impact of nucleofection on translational machinery has important implications for therapeutics currently under development based on the delivery of mRNA, DNA, and small interfering RNA. Strategies to circumvent eIF2α phosphorylation and other downstream effects of activating GCN2 and PERK will facilitate further advancement of nucleic acid-based therapies.